Menganalisis Menejemen Koprasi Terhadap Koprasi Dalam Membentek Dadan Usaha - Rosi, Fahrur; Yasin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Cooperatives in Indonesia, as a popular financial institution since the era of President Suharto, are defined by Law No. 25/1992 and Moh. Hatta. Cooperatives are business entities based on the principles of people's economy and the principle of kinship, as well as joint efforts to improve economic life through mutual assistance.Management, as a process of organizing the activities of individuals or groups, is crucial for achieving the goals of cooperatives. The definition of management includes planning, organizing, actuating, and controlling. Experts such as G. Terry and Griffin define management as a dynamic and continuous process that incorporates these elements. Cooperative management, as formulated by Peter Davis, is a professional activity involving the management of the cooperative's values and assets by competent individuals, with the aim of empowering all its members. Cooperative management not only uses general management methods but also emphasizes member participation and involvement in decision-making, differing from the management of other organizations. Further discussion includes the functions and implementation of cooperative management, which consist of planning, organizing, actuating, and controlling. Each function is explained in detail, including the division of tasks within the cooperative organization, such as member meetings, management, and supervision. The cooperative management process involves identification and evaluation, formulation of strategic and tactical plans, as well as preventive and corrective supervision to ensure the cooperative's objectives are achieved effectively and efficiently.